Anti‐SSA antibodies are present in immunoglobulin preparations. Issue 4 (13th November 2014) - van der Molen, Renate G.; Hamann, Dörte; Jacobs, Joannes F.M.; van der Meer, Arnold; de Jong, Jan; Kramer, Christine; Strengers, Paul F.W.; van der Meer, Jos W.M.
<x xml:space="preserve">Abstract</x> Background Anti‐SSA autoantibodies are among the most frequently detected autoantibodies and have traditionally been associated with Sjögren's syndrome (SjS) and systemic lupus erythematosus. The unexpected finding of anti‐SSA antibodies in a patient with common variable immunodeficiency disorder (CVID) treated with intravenous immunoglobulin (IVIG), who developed discoid lupus erythematosus, prompted us to investigate the presence of anti‐SSA antibodies in IVIG preparations. Since anti‐SSA antibodies may be present in apparently healthy individuals without overt autoimmune features, IVIG preparations may also contain anti‐SSA antibodies. Study Design and Methods IVIG consists of polyclonal immunoglobulin G isolated from the plasma of more than 1000 blood donors. Several IVIG batches from different suppliers and serum samples of patients receiving these IVIG products were tested for the presence of anti‐nuclear antibodies (ANAs) and extractable nuclear antibodies (ENAs). In addition, we tested several plasma pools for the presence of anti‐SSA and subsequent serum samples of individual donors. Results Several CVID‐patients receiving IVIG tested positive for ANA and anti‐SSA. The IVIG products administered also contained clearly detectable concentrations of these antibodies. The frequency of apparently healthy blood donors with anti‐SSA positivity was 0.69% and one of 1894 donors (0.05%) showed a very high titer of anti‐SSA of more than 10, 000 U/mL. Conclusion Anti‐SSA is present in IVIG products and in blood donors without clinical symptoms. IVIG replacement can interfere with ANA and ENA serology by passive transfer of autoantibodies. We hypothesize that such autoantibodies may be causally related to disease manifestations in some recipients.